2016
DOI: 10.1038/ejhg.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

‘You should at least ask’. The expectations, hopes and fears of rare disease patients on large-scale data and biomaterial sharing for genomics research

Abstract: Within the myriad articles about participants' opinions of genomics research, the views of a distinct group - people with a rare disease (RD) - are unknown. It is important to understand if their opinions differ from the general public by dint of having a rare disease and vulnerabilities inherent in this. Here we document RD patients' attitudes to participation in genomics research, particularly around large-scale, international data and biosample sharing. This work is unique in exploring the views of people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 30 publications
1
107
1
2
Order By: Relevance
“…Participants with genetic exceptionalist views and selfreported familiarity with genomics had the greatest odds (nearly 6 times greater) of being willing to donate their DNA information (compared to those who were unfamiliar with genomics and did not have exceptionalist views). Such willingness among those with personal familiarity has been seen in patient groups who want their data to be put to good use for future disease prevention, or to help future generations within their own family [34,35]. Many of those most willing to donate were also professionals working in the genomics field.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with genetic exceptionalist views and selfreported familiarity with genomics had the greatest odds (nearly 6 times greater) of being willing to donate their DNA information (compared to those who were unfamiliar with genomics and did not have exceptionalist views). Such willingness among those with personal familiarity has been seen in patient groups who want their data to be put to good use for future disease prevention, or to help future generations within their own family [34,35]. Many of those most willing to donate were also professionals working in the genomics field.…”
Section: Discussionmentioning
confidence: 99%
“…23 Nonetheless, a survey of patients with rare diseases revealed that they are positively disposed toward (genomics) research and toward allowing data and even biosamples to be shared internationally. 24 It is encouraging to observe that those who have most at stake generally come out in favor of secondary use of their data. We would assume that patients would overwhelmingly welcome and support the learning healthcare system, provided there are adequate safeguards for personal data protection.…”
Section: Can We Overcome the Current Research Vs Practice Divide?mentioning
confidence: 98%
“…Through these collaborative efforts, there have been marked improvements in disease classification and coding, with a growing acceptance of standard nomenclature and development of policies for ethical and secure data sharing for rare and genetic diseases . This is being complemented by significant developments in genomics knowledge and technologies, which are driving faster and more accurate diagnoses and the development of specific treatments, labeled as “precision medicine” or “personalized medicine.” While the benefits to individuals of such targeted approaches are clear, the same knowledge and technologies are providing opportunities to better understand and assess the impact of disease at a population level.…”
Section: Objectives and Progress On Objectives 2011–2020 Now 2017mentioning
confidence: 99%